Building Sociomuseology: an analysis of the PhD’ theses defended in Museology at ULHT (2008-2020) (Cadernos de Sociomuseologia, 2020)
This article aims to present preliminary data from an investigation that seeks to help to understand the contributions of thesis and dissertations defended at the Museology Department of Universidade Lusófona for the development of Sociomuseology between the years 2008 and 2020. This study has among its concerns understand how the production of knowledge in the area of Museology is being structured, based on research developed at ULHT, and the emergence of the School of Thought of Sociomuseology. In this article we focus our analysis on the doctoral thesis, analyzing 46 papers defended between 2008 and 2020, which corresponds to all the researchs located for the period. We discussed this production through the analysis of the treated themes, covered geographical spaces and a brief profile of the researchers involved, seeking to point out interpretations and possibilities for understanding Sociomuseology.Keywords: Sociomuseology, Museology, Doctoral Thesis, Universidade Lusófona.